Pengaruh Social Media Marketing dan Electronic Word of Mouth Terhadap Purchase Intention Melalui Brand Image : Studi pada Pengguna Lazada di Kota Denpasar - Novia Indah Dewanti; I Wayan Santika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
The increasing competition in the marketplace has made Lazada one of the platforms that is falling behind compared to several competitors, particularly in terms of sales or purchase intention. Several factors contribute to this, including social media marketing, audience opinions and reviews, and Lazada's brand image. This study evaluates the influence of social media marketing and electronic word of mouth (E-WOM) on purchase intention through brand image. The aim of this research is to determine the impact of social media marketing and E-WOM on purchase intention, with brand image serving as a mediator. The study was conducted among Lazada marketplace users in Denpasar City, involving 160 respondents using purposive sampling. Data was collected through a questionnaire distributed via Google Forms. The collected data was analyzed using path analysis and Sobel test techniques. The findings indicate that all hypotheses are supported. Social media marketing positively and significantly influences brand image; E-WOM positively and significantly influences brand image; social media marketing positively and significantly impacts purchase intention; E-WOM positively and significantly impacts purchase intention; brand image positively and significantly influences purchase intention. Additionally, brand image positively and significantly mediates the effects of social media marketing and E-WOM on purchase intention. The theoretical implications of this study support consumer behavior theories and previous research. The practical implications suggest that Lazada's management should prioritize social media marketing, E-WOM, and brand image to enhance purchase intention.